2004
DOI: 10.1038/sj.emboj.7600077
|View full text |Cite
|
Sign up to set email alerts
|

DNA topology, not DNA sequence, is a critical determinant for Drosophila ORC–DNA binding

Abstract: Drosophila origin recognition complex (ORC) localizes to defined positions on chromosomes, and in follicle cells the chorion gene amplification loci are well-studied examples. However, the mechanism of specific localization is not known. We have studied the DNA binding of DmORC to investigate the cis-requirements for DmORC:DNA interaction. DmORC displays at best six-fold differences in the relative affinities to DNA from the third chorion locus and to random fragments in vitro, and chemical probing and DNase1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
236
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(253 citation statements)
references
References 47 publications
10
236
1
4
Order By: Relevance
“…Unlike in S. cerevisiae, ORC purified from higher eukaryotes shows little or no sequence specificity in vitro (Vashee et al 2003;Remus et al 2004). Together these results might suggest that origin selection and replication initiation are random or stochastic events in higher eukaryotes, but numerous studies have identified specific origins of replication as well as ORC binding at specific and reproducible chromosomal locations (Austin et al 1999;Ladenburger et al 2002;Karnani et al 2010;MacAlpine et al 2010).…”
Section: Chromatin and The Regulation Of Replication Originsmentioning
confidence: 96%
“…Unlike in S. cerevisiae, ORC purified from higher eukaryotes shows little or no sequence specificity in vitro (Vashee et al 2003;Remus et al 2004). Together these results might suggest that origin selection and replication initiation are random or stochastic events in higher eukaryotes, but numerous studies have identified specific origins of replication as well as ORC binding at specific and reproducible chromosomal locations (Austin et al 1999;Ladenburger et al 2002;Karnani et al 2010;MacAlpine et al 2010).…”
Section: Chromatin and The Regulation Of Replication Originsmentioning
confidence: 96%
“…However, quantitative analysis of ORC binding suggested that DNA topology might also be an important factor. Indeed, purified ORC has a 30-fold higher affinity for negative supercoiled DNA, which can be generated in the cell by removal of histones with chromatin remodeling complexes (Remus et al, 2004). Supporting data to this hypothesis came from chromatin immunoprecipitation experiments showing that Myb and Mip120 (Beall et al, 2002), components of the Myb complex, and E2f1 (Bosco et al, 2001), one of the two E2F subunits, bind to the chorion replication origin.…”
Section: Chorion Gene Amplificationmentioning
confidence: 99%
“…In particular, ORC-binding sites coincide with DNAse I hypersensitive sites and histone modifications of active chromatin [8792]. The majority of the ORC binding sites coincide with transcription regulatory elements, such as promoters and transcriptional enhancers [85].…”
Section: Replication Timingmentioning
confidence: 99%